Artificial evolution : 12th International Conference, Evolution Artificielle, EA 2015, Lyon, France, October 26-28, 2015, revised selected papers /: 12th International Conference, Evolution Artificielle, EA 2015, Lyon, France, October 26-28, 2015, revised selected papers. (2016) - Unknown
No abstract available